Impact of climate change and adaptations for cultivation of millets in Central Sahel - Abubakar, Ahmed; Ishak, Mohd Yusoff; Uddin, Md. Kamal; Sulaiman Zangina, Aminu; Ahmad, Mohammad Hadi; Shehu Danhassan, Samir (Springer Nature, 2023)
Climate change has impacted agricultural production systems, especially in the Sahel region, which is fragile climatically, politically, and economically. This region is of particular concern due to its rising population and strategic importance on the African continent. Our review focused on the impact of climate change on millet production in the Central Sahel and aimed to identify adaptation strategies by the farmers. This review shows that increased temperature has a negative impact on millet yield and growth parameters. Other climatic factors signifcantly afecting millet production in the Central Sahel include drought, desertifcation, dry spells, rainfall variability, and wind. Projected data suggests a decline in millet production in northern, central, and western Mali by 21%, 20%, and 18%, respectively, by 2030. Additionally, there is an anticipated 17% decrease in pearl millet production in Sub-Saharan Africa by 2050 under future climate change projections. Nevertheless, farmers in the Central Sahel have devised a variety of indigenous climate change adaptation strategies to sustain millet production. These adaptation strategies encompass Zai, half-moon, stone-line, and intercropping. These adaptation practices have proven efective in mitigating the efects of climate change on millet production in the Sahel region. This review suggests strengthening farmers' adaptive capacity to climate change, promoting regional knowledge, integrating millet as a fundamental crop group for food security in the Central Sahel, adopting zero-tillage or minimum-tillage practices during crop production, diversifying crops, and providing heat- and drought-tolerant crop varieties.